Children and Youth Interest Education Establishment as Non-Formal Educational Environment in Latvia - Svareniece, Benita; Katane, Irēna (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
These days sustainability of education becomes more actual the guarantor of which appears to be the availability and multiplicity of education for every human being during the lifetime where the non-formal education takes a significant place. The aim of the article is to update the role of the interest education of children and young people in the context of life-long education when publishing the results of the completed theoretical and empirical research in the sphere of the non-formal education. The empirical research ’Interest education in Latvia and the role of the institutions of interest education’ has been accomplished within the frameworks of the working group of the constructive board of headmasters of the interest educational institutions of Latvia. The results of the survey of the children and young people acknowledge that there is a wide spectrum of motives of choosing the interest education. The choice and popularity of the programmes of the interest education have been defined by several groups of factors. It is important to offer possibilities to attend different interest groups both in the country and in towns thus gaining new out-of –school experience that can further largely result on choosing the career objectives. Both –the researches and the personal experience of the author affirm that the centres of the interest education of the children and youth are the sub-systems of multifunctional environment of the non-formal education in the total environment of the education of Latvia.